Isolated Central Sulcus Hemorrhage: A Rare Presentation Most Frequently Associated with Cerebral Amyloid Angiopathy. (11th December 2012) - Chamarthy, Murthy R.; Kumar, Yogesh; Meszaros, Michael D.; Shah, Ankit; Rosovsky, Mark A.
Abstract : Central sulcus hemorrhage is a rare imaging finding that can be related to cerebral amyloidosis in a normotensive non-traumatic elderly patient and present as an isolated finding or in association with other areas of involvement. We report a case presenting with an isolated central sulcus hemorrhage on computed tomography. Further imaging work-up excluded other potential causes of peripheral hemorrhages and established a putative diagnosis of cerebral amyloidosis.